2007
DOI: 10.1371/journal.pone.0001141
|View full text |Cite
|
Sign up to set email alerts
|

Austro-Asiatic Tribes of Northeast India Provide Hitherto Missing Genetic Link between South and Southeast Asia

Abstract: Northeast India, the only region which currently forms a land bridge between the Indian subcontinent and Southeast Asia, has been proposed as an important corridor for the initial peopling of East Asia. Given that the Austro-Asiatic linguistic family is considered to be the oldest and spoken by certain tribes in India, Northeast India and entire Southeast Asia, we expect that populations of this family from Northeast India should provide the signatures of genetic link between Indian and Southeast Asian populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 37 publications
6
70
0
Order By: Relevance
“…1,18 Mutations are recorded by comparing with the revised Cambridge reference sequence (rCRS). 19 All the individuals were allocated into specific haplogroup based on their control-region information; the assignments were further confirmed by typing additional diagnostic coding-region mutations according to the reconstructed phylogenetic trees of East Asian, 1,20-25 South Asian 5,7,12,[26][27][28][29][30][31][32][33] and Southeast Asian [34][35][36][37][38] (Supplementary Table S1, Supplementary Material online). For the mtDNA sample of interest, entire genome was amplified and sequenced as described elsewhere.…”
Section: Dna Amplification Sequencing and Quality Controlmentioning
confidence: 99%
“…1,18 Mutations are recorded by comparing with the revised Cambridge reference sequence (rCRS). 19 All the individuals were allocated into specific haplogroup based on their control-region information; the assignments were further confirmed by typing additional diagnostic coding-region mutations according to the reconstructed phylogenetic trees of East Asian, 1,20-25 South Asian 5,7,12,[26][27][28][29][30][31][32][33] and Southeast Asian [34][35][36][37][38] (Supplementary Table S1, Supplementary Material online). For the mtDNA sample of interest, entire genome was amplified and sequenced as described elsewhere.…”
Section: Dna Amplification Sequencing and Quality Controlmentioning
confidence: 99%
“…13,19,38 Although AA-speaking populations are considered as the oldest groups in India, there are many competing theories on their origin and subsequent settlement. The AAs have three sub-families such as Mundari, Mon-Khmer and Khasi-Khmuic in India and they display region-specific distribution.…”
Section: Sub-himalayan Gene Pools: Reservoirs Of Variationmentioning
confidence: 99%
“…This is reflected by genetic studies that suggested Northeast India as an important corridor for human dispersals, whereas Nepal Himalaya as a barrier for bidirectional gene flow. 16,19 Apart from these Himalayan regions, there are some interesting outermost sub-Himalayan zones in the plains of East India, which are known as Terai and Duars (also Dooars). Unlike the Himalaya, these areas have characteristically unique and diverse ethnic populations belonging to four different linguistic groups such as TB, Austro-Asiatic (AA), Indo-European (IE) and Dravidian (DR).…”
Section: Introductionmentioning
confidence: 99%
“…An increased number of complete mtDNA sequences refined the phylogeography and phylogeny of M31 and identified a sister clade (M31a2) to Andaman-specific M31a1 in East India (Barik et al 2008). A third branch (M31c) was subsequently identified among populations of Northeast India (Wang et al 2011;Reddy et al 2007;Fornarino et al 2009). The discovery of M31a2 in East India was particularly important because the separation time between this clade and its sister, M31a1, at ~25 ka (Barik et al 2008) is half that previously suggested for the age of M31 overall (Thangaraj et al 2005).…”
mentioning
confidence: 91%